2014
DOI: 10.1002/ptr.5180
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone Increases the Expression of Adipocyte‐Specific Genes in 3 T3‐L1 Adipocyte

Abstract: Umbelliferone (UMB), a natural product of coumarin family, has been shown to reduce blood glucose and to improve lipid profiles in streptozotocin (STZ)-induced diabetic rats. Our objective was to examine the effect of UMB on adipogenesis by investigating its stimulatory effect on lipid accumulation and mRNA expression of adipogenic transcription factors and adipocyte-specific genes in 3 T3-L1 preadipocyte culture. An Oil Red O staining was used to monitor lipid accumulation, and we found that UMB treatment at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…UMB has been reported to exhibit neuroprotective effects in MPTP-induced mouse model and cross the blood-brain barrier, indicating that UMB has the potential to protect neuron from apoptosis [9]. UMB positively regulates peroxisome proliferator-activated receptor-␥ (PPAR-␥) activity and this action is involved in amelioration of metabolic disorders and alcohol-induced fatty liver [10][11][12]. PPAR-␥, belonging to the nuclear hormone receptor superfamily, has been certified as an important regulator of apoptosis, oxidative stress and inflammation [13][14][15], and also plays a significant role in the neuroprotection against cerebral ischemia-reperfusion injury [16].…”
mentioning
confidence: 99%
“…UMB has been reported to exhibit neuroprotective effects in MPTP-induced mouse model and cross the blood-brain barrier, indicating that UMB has the potential to protect neuron from apoptosis [9]. UMB positively regulates peroxisome proliferator-activated receptor-␥ (PPAR-␥) activity and this action is involved in amelioration of metabolic disorders and alcohol-induced fatty liver [10][11][12]. PPAR-␥, belonging to the nuclear hormone receptor superfamily, has been certified as an important regulator of apoptosis, oxidative stress and inflammation [13][14][15], and also plays a significant role in the neuroprotection against cerebral ischemia-reperfusion injury [16].…”
mentioning
confidence: 99%
“…Umbelliferone can act as an antihyperglycemic agent in STZ‐induced type 1 diabetic rats (Ramesh and Pugalendi, ). It has been reported that UMB can stimulate adipogenesis in 3 T3‐L1 cells (Naowaboot et al, ). A recent study found that UMB and 4‐methylumbelliferone reduced the hypertriglyceridemia and hyperglycemia in HFD‐induced obese mice (Sim et al, ).…”
Section: Introductionmentioning
confidence: 99%